2015
DOI: 10.1590/0104-0707201500002970014
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality in Patients With Acute Myocardial Infarction

Abstract: The aim of this study was to describe sleep quality and to identify associated factors in patients hospitalized with acute myocardial infarction. A descriptive and cross-sectional study was conducted with 113 patients (70.8% men, mean age 59.7 years). An instrument was used for sociodemographic and clinical characterization and the Pittsburgh Sleep Quality Index. Results showed that 71.7% of participants had poor sleep quality and over 64% slept six hours or less per night. The presence of diabetes mellitus, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 38 publications
0
21
0
8
Order By: Relevance
“…Likewise, the absence of the DC determined the absence of the ND. This DC is related to the presence of alterations in the amount and quality of sleep of hospitalized patients with ACS, and several studies present data that corroborate this finding (Alcântara, Peacock, Davidson, Hiti, & Edmondson, ; Andrechuk & Ceolim, ; Schiza et al., ). Another study demonstrated that patients with ACS who had less than 7 hr of sleep were associated with short sleep duration, with a high risk (greater than 50%) of death after 1 year of initial or recurrent ACS (Alcántara et al., ).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Likewise, the absence of the DC determined the absence of the ND. This DC is related to the presence of alterations in the amount and quality of sleep of hospitalized patients with ACS, and several studies present data that corroborate this finding (Alcântara, Peacock, Davidson, Hiti, & Edmondson, ; Andrechuk & Ceolim, ; Schiza et al., ). Another study demonstrated that patients with ACS who had less than 7 hr of sleep were associated with short sleep duration, with a high risk (greater than 50%) of death after 1 year of initial or recurrent ACS (Alcántara et al., ).…”
Section: Discussionmentioning
confidence: 64%
“…This can interfere with the quality and quantity of sleep (Costa & Ceolim, ), considering both extrinsic and associated intrinsic factors. This may be a limiting factor in the study; however, a consensus was not found on the best time for sleep assessment in hospitalized patients with ACS, because previous studies performed this evaluation at different times (Andrechuk & Ceolim, ; Storti et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations